Anatomical movement replicator applied to activities in ionizing radiation fields (Brazilian Journal of Radiation Sciences (BJRS), 2021)
The aim of this work is to demonstrate the need to develop more efficient means for radiological protection, making use of the latest automation and robotics technologies. A manipulator model has been developed that has technological differentials that can positively influence the performance and cost of remote manipulation. The built-in equipment has a Slave manipulator, developed without using semiconductor elements. They are housed in the control center, which is attached to the manipulator via umbilical cord, facilitating the equipment adaptation in hot cells and other working environments. The arrangement of the joints and the links, have similarities with the anatomy of the human arm, improving the instinctively of the operation. To demonstrate its technological feasibility, a prototype Master-Slave manipulator was designed, and built using three control programs, which were written exclusively for this work. It was also designed to reduce construction and operation costs, making it accessible to most areas. The results obtained with the prototype construction are shown to be promising, providing an incentive to continue the development of manipulators using similar technologies. The equipment, obtained satisfactory results in relation to the operability, being able to perform movement tasks of loads, as foreseen in the project.